Fibrosis: a structural modulator of sinoatrial node physiology and dysfunction - Csepe, Thomas A.; Kalyanasundaram, Anuradha; Hansen, Brian J.; Zhao, Jichao; Fedorov, Vadim V. (Frontiers in Physiology, 2015)
Heart rhythm is initialized and controlled by the Sinoatrial Node (SAN), the primary pacemaker of the heart. The SAN is a heterogeneous multi-compartment structure characterized by clusters of specialized cardiomyocytes, enmeshed within strands of connective tissue or fibrosis. Intranodal fibrosis is emerging as an important modulator of structural and functional integrity of the SAN pacemaker complex. In adult human hearts, fatty tissue and fibrosis insulate the SAN from the hyperpolarizing effect of the surrounding atria while electrical communication between the SAN and right atrium is restricted to discrete SAN conduction pathways. The amount of fibrosis within the SAN is inversely correlated with heart rate, while age and heart size are positively correlated with fibrosis. Pathological upregulation of fibrosis within the SAN may lead to tachycardia-bradycardia arrhythmias and cardiac arrest, possibly due to SAN reentry and exit block, and is associated with atrial fibrillation, ventricular arrhythmias, heart failure and myocardial infarction. In this review, we will discuss current literature on the role of fibrosis in normal SAN structure and function, as well as the causes and consequences of SAN fibrosis upregulation in disease conditions.